English in medicine : A course in communication skills - Glendinning, Eric H.; Holmstrom, Beverly A. S. (New York Cambridge University Press, 2005)
English in Medicine is a course for doctors, medical students and other medical professionals who need to communicate with patients and medical colleagues. Each of the seven units focuses on one area of doctor-patient communication, from history-taking and examination to diagnosis and treatment. The course develops all four skills through a wide variety of activities.
Keywords: Ngôn ngữ Anh